Human Resource Policies’ Effect on Teacher Career Progression: Unravelling Systemic and Structural Teacher Career Advancement Barriers - Chisiri, Benard; Munikwa, Simbarashe; Tapera, Julius (CV. Literasi Indonesia, 2024)
This study sought to find out secondary school teachers’ perceptions of the impact of human resource (stay) policies on secondary school teachers' career progression in Bikita District of Zimbabwe. The flexible question that this research sought to find answers to is whether human resource (stay) policies are not teacher career progression retardants that contribute towards the production of career progression bonsaied secondary school teachers. The study adopted a qualitative approach in which an interpretivist philosophy was applied. This study is hinged on an inference line of inquiry to find a cause and effect on human resource stay policies and teacher career progression. A hybridized research design comprising multiple case studies and a phenomenological design was adopted. Referral snowballing sampling was employed and six Focus Group Discussions of six members per group were conducted on a sample of 36 teachers from selected secondary schools from the district. Data were analyzed thematically The study established that the training and development policy, reward policy, and promotion policy, which are structural and systemic components at the stay level of the human resource function contain physiognomies that constrict the career progression of teachers in the Bikita District: The study concluded that existing policies discourage internal vertical progression as well as external mobility of teachers to other ministries and external organizations.